KIF5A Promotes Bladder Cancer Proliferation In Vitro and In Vivo. (3rd July 2019) - Tian, Da-Wei; Wu, Zhou-Liang; Jiang, Li-Ming; Gao, Jie; Wu, Chang-Li; Hu, Hai-Long
Abstract : Background . Bladder cancer is a common malignancy with uncontrolled and rapid growth. Although lots of the important regulatory networks in bladder cancer have been found, the cancer-relevant genes remain to be further identified. Methods . We examined the KIF5A expression levels in bladder cancer and normal bladder tissue samples via immunohistochemistry and observed the effect of KIF5A on bladder tumor cell proliferation in vitro and in vivo . Additionally, a coexpression between KIF5A and KIF20B in tumor tissues was explored. Results . KIF5A expression level was higher in the bladder cancer tissues than in the adjacent nontumor tissues. Patients with higher KIF5A expression displayed advanced clinical features and shorter survival time than those with lower KIF5A expression. Moreover, KIF5A knockdown inhibited bladder cancer cell proliferation, migration, and invasion demonstrated in vivo and in vitro . In addition, coexpression was found between KIF5A and KIF20B in tumor tissues. Conclusion . The results demonstrated that KIF5A is a critical regulator in bladder cancer development and progression, as well as a potential target in the treatment of bladder cancer.